Social Advertising & Consumer Awareness In Context To Swachh Bharat Abhiyan - Sharma, Navneet; Sharma, Dr. Trishu (The journal of contemporary issues in business and government, 2021)
The term media is not just restricted to news dissemination whereas it has a broader spectrum with the help of various platform and audience are always presume to be passive and strongly get effected and influence by the media message so there are chances that the social advertising campaign work as a strong media message and influence the behavior of the receptive audience. The idea of social marketing as an applied concept is commonly used worldwide as an approach to attempt to guide people to follow socially responsible practices and enhance public welfare As part of social marketing, social advertising must be referred to as social awareness advertising, which focuses mainly on social problems such as national integration, pollution, family advertising. The primary purpose of this type of public service advertising is to educate the masses through hard hitting educational messages Face-to-face interviews were conducted with 250 individuals using a framework questionnaire to understand the efficacy of these social movements to examine their effects on society as a whole.